PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWANDENGAN KERPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PTBANK PEMBANGUNAN DAERAH JAWA TIMUR CABANG SIDOARJO - LAILY ALFANY, NURIL (Jurnal Ilmu Manajemen (JIM), 2017)
Abstract Bank Pembangunan Daerah Jawa Timur (Bank Jatim) is a general bank and Regional Enterprises which is owned by East Java Province Government. Bank Jatim has assets for more than IDR 30 Trillion with 36 brand offices that are spread along all over Indonesia. Bank Jatim just achieved reward as the best Bank in Retail Bank Service that is given by Indonesian Banking Award 2016. Also, Bank Jatim also got achievement from TOP BUMD as TOP BPD Manajemen SDM and IT 2016. The achievements and rewards that are achieved by Bank Jatim surely supported by good Employee performance. This employee performance cannot separated from emotional intelligence employee and job satisfaction for the employee. The purpose of this study is to testing and analyzing the influence of emotional intelligence toward employess performance through job satisfaction as a intervening variable. This is a causal research with quantitative approach. The sample collecting technique is using sample saturation with 54 respondents of customer service, service assistant,teller and credit division in Bank Jatim Sidoarjo branch. The statistical analysis used is Partial Least Square (PLS) with the support of smartPLS software. Result of the study explained that emotional intelligence has positive and significant effect on employee performance. Emotional intelligence has positif and significant effect on job satisfaction. Job satisfaction has positif and significant effect on employee performance. Job satisfaction intervening the influence of emotional intelligence on employee performance. Keywords: Emotional Intelligence, Job Satisfaction, Employee Performance